A6.11 Evaluation of soluble biomarkers of synovial inflammation using weighted joint counts assessed clinically and on ultrasound imaging. (13th February 2015) - Burska, AN; Hensor, EMA; Nam, JL; Kozera, L; Emery, P; Wakefield, RJ; Morgan, AW
Abstract : Background: Synovial inflammation is known to play a central role in the development of bony erosions and articular cartilage degradation in RA. We aimed to determine if circulating metalloproteinase-3(MMP-3), hyaluronic acid (HA), serum amyloid A(SAA), interleukin 6(IL-6) and calprotectin (S100A8/A9) would outperform CRP as surrogate biomarkers for synovitis detection. Methods: Patients were recruited to a randomised controlled trial; 1 baseline samples and clinical data were included in this analysis. Patients fulfilled 1987 ACR RA classification criteria, had 3–12 month symptom duration, active disease (DAS44 > 2.4) and were DMARD naïve. In a subset, grey scale (GS) and power Doppler (PD) ultrasound (US) semi-quantitative scores (0–3) were assigned to wrists, MCPs and PIPs 2 and 3 and MTPs 1–5 bilaterally. Both counts (joints scoring GS > 1, PD > 0, simultaneously GS > 1 and PD > 0) and score totals were created. To reflect synovitis burden, joint measures were weighted by multiplying each joint's score by a relative area weight, 2 before summating. Samples were tested for MMP-3, HA, SAA, IL-6, S100A8/A9 using research-use-only multiplex platform IMPACT (Immunological Multi-Parameter Chip Technology) (Roche Professional Diagnostics, Germany), 3 CRP was measured in the routine lab. We calculated bootstrapped confidence intervals (CI) for the differences between CRP and the other markers in the strength of Kendall's tau-a rank correlation with the joint assessments using Stata 13.1. Results: Fifty-nine patients were included: mean (SD) age 52.7 (13.8) years, 71% female, median (IQR) disease duration 1.0 (0.7, 1.6) months. Marker values [median (IQR)] were CRP 16.4 (8.2, 52.0); MMP3 58.9 (42.1, 119.3); HA 36.5 (20.5, 70.2); SAA 36.5 (6.3, 249.0); IL-6 46.3 (21.4, 69.1); S100 A8/A9 12.1 (8.6, 15.2). Associations were stronger when joint weights were used, particularly for CRP and MMP3 (data not shown), but remained weak-to-moderate; the strongest were between weighted clinical joint counts and CRP. The association with SJC28 was substantively stronger for CRP (tau = 0.46) than for any of the other markers and was significantly stronger than for HA (tau = 0.24; difference 0.04–0.44). Similar values were obtained using 28- or 44-joint clinical counts. CRP, MMP3 and IL-6 were associated with US to a comparable degree (tau circa 0.30); associations with US for SAA and S100A8/A9 were slightly weaker than CRP, although differences were not significant. Conclusion: Weighting for joint area improved correlation with circulating inflammatory markers. None of the markers outperformed CRP as a surrogate biomarker of synovitis across the full range of observed values. We intend to investigate their utility in patients with low/normal CRP. Funding: Roche Professional Diagnostics provided free of charge access to the IMPACT platform and IMPACT reagents. This work was also supported by grants from Arthritis Research UK and the NIHR. References: Nam JL, Villeneuve E, Hensor EMA, et al . Ann Rheum Dis 2014; 73 :75. Lansbury J, Haut DD. Am J Med Sci 1956; 232 :150. Claudon A, Vergnaud P, Valverde C, et al . Clin Chem 2008; 54 :1554.